Broadband yellow and white emission from large octahedral tilting in (110)-oriented layered perovskites: imidazolium-methylhydrazinium lead halides. Issue 14 (29th March 2023) - Drozdowski, Dawid; Fedoruk, Katarzyna; Kabanski, Adam; Maczka, Mirosław; Sieradzki, Adam; Gagor, Anna
Abstract : New (110)-oriented 2D HOIPs exhibit record octahedral tilting implying broadband white and yellow photoluminescence, and an order–disorder symmetry-breaking phase transition at high temperatures. Abstract : Hybrid organic–inorganic perovskites (HOIPs) are presently on the cutting edge of contemporary materials chemistry providing excellent and tuneable optoelectronic properties. Here we report the synthesis, crystal structures, and linear optical, and dielectric properties of two newcomers to the family of two-dimensional (2D) HOIPs – IMMHyPbBr4 and IMMHyPbCl4 (IMPB and IMPC ), respectively, where IM = imidazolium, MHy = methylhydrazinium) which adopt rarely reported alignment of PbX6 octahedral layers (X = Br, Cl), described as (110)-cut derivatives of 3D perovskites, with IM + situated at the interlayer and MHy + at intralayer sites. Both materials exhibit phase transitions with the high-temperature phase of monoclinic P 2/ c symmetry with both organic cations and the linking halide anion being disordered. On cooling, at 344.5 K (375.4 K) for IMPB (IMPC ) a P 2/ c → P 21 / c symmetry breaking occurs which induces strong tilting of octahedral layers, with the lowest Pb–Xlink –Pb angle (143° for IMPC, Xlink = linking halide) ever reported for this class of compounds. Dielectric studies reveal a well-defined single dipolar relaxation process in the low temperature range from 150 K (170 K) to 188 K (230 K) for IMPB (IMPC ), associated with the change in dynamics of the MHy + cation. With the use of linear optical measurements, we demonstrate that both compounds exhibit broadband emission with a large Stokes shift attributed to self-trapped excitons. The emission colour changes with temperature and IMPB is the first example of a mixed-organic cation perovskite showing white-light emission near 200 K. The structure–physiochemical property relationship is discussed with reference to other (110)-oriented lead halides.